2021
DOI: 10.1038/s41598-021-84174-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA traces the origin of honey by identifying plants, bacteria and fungi

Abstract: The regional origin of a food product commonly affects its value. To this, DNA-based identification of tissue remains could offer fine resolution. For honey, this would allow the usage of not only pollen but all plant tissue, and also that of microbes in the product, for discerning the origin. Here we examined how plant, bacterial and fungal taxa identified by DNA metabarcoding and metagenomics differentiate between honey samples from three neighbouring countries. To establish how the taxonomic contents of hon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 75 publications
4
53
0
1
Order By: Relevance
“…In line with previous work (47,49), our pipeline revealed that the majority of DNA traces contained in honey samples did not belong to plants (Figure 3a). To better understand the importance of this diversity and their relationship with honeybees, we first used a text mining approach to categorize their relationship with honeybees based on current literature (See method and Sup.…”
Section: Non-invasive Characterisation Of the Hive Pathogens And The Dynamics Of Core And Non-core Honeybee Gut Microbiomesupporting
confidence: 91%
See 2 more Smart Citations
“…In line with previous work (47,49), our pipeline revealed that the majority of DNA traces contained in honey samples did not belong to plants (Figure 3a). To better understand the importance of this diversity and their relationship with honeybees, we first used a text mining approach to categorize their relationship with honeybees based on current literature (See method and Sup.…”
Section: Non-invasive Characterisation Of the Hive Pathogens And The Dynamics Of Core And Non-core Honeybee Gut Microbiomesupporting
confidence: 91%
“…The assessment of the complex ecological niche that honeybees occupy has only recently begun to be examined through the use of shotgun metagenomics (47)(48)(49). In this study we have developed a direct approach for shotgun metagenomics (Direct-SM) and a bioinformatic pipeline to assess the species composition of honey samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data used for our study derive from a previous paper [ 23 ], in which we ask whether the taxonomic contents of honey might be used to identify the country of origin [ 23 ]. In the current study, we approach the same data from a novel perspective, asking what the taxonomic and functional groups detected in honey will reveal about the honeybee’s role in its environment.…”
Section: Introductionmentioning
confidence: 99%
“…NGS methods have recently been investigated to distinguish between closely related eukaryotic species [21,22] and to detect food origins [23], the presence of toxic species [24], allergens [25], as well as other cases of adulteration [20,26,27], both accidental and economically motivated. However, the application of NGS technology is not without limitations.…”
Section: Introductionmentioning
confidence: 99%